A Novel Diamond Ring Fiber-Based Surface Plasmon Resonance Sensor - Ng, Wee Lit; Rifat, Ahmmed A.; Wong, Wei Ru; Mahdiraji, Ghafour Amouzad; Adikan, Faisal Rafiq Mahamd (Springer Verlag (Germany), 2018)
We propose a highly sensitive novel diamond ring fiber (DRF)-based surface plasmon resonance (SPR) sensor for refractive index sensing. Chemically active plasmonic material (gold) layer is coated inside the large cavity of DRF, and the analyte is infiltrated directly through the fiber instead of selective infiltration. The light guiding properties and sensing performances are numerically investigated using the finite element method (FEM). The proposed sensor shows a maximum wavelength and amplitude interrogation sensitivity of 6000 nm/RIU and 508 RIU−1, respectively, over the refractive index range of 1.33–1.39. Additionally, it also shows a sensor resolution of 1.67 × 10−5 and 1.97 × 10−5 RIU by following the wavelength and amplitude interrogation methods, respectively. The proposed diamond ring fiber has been fabricated following the standard stack-and-draw method to show the feasibility of the proposed sensor. Due to fabrication feasibility and promising results, the proposed DRF SPR sensor can be an effective tool in biochemical and biological analyte detection.